Gravitational instability of vacuum and the cosmological problem - Fomin, P.I. (Вопросы атомной науки и техники, 2013)
It is shown that, with the account of the gravitational interaction, the physical vacuum can spontaneously partially "dissociate" into particles and antiparticles without violation of any conservation laws. Possible cosmological significance of this effect is discussed. A "vacuum cosmological model" is formulated, in which vacuum is taken as the initial state of the Metagalaxy. A generalization of the classical cosmological Einstein equations is made which allows one to take into account phenomenologically the e®ect of gravitational instability of vacuum. This work was reported at the seminar of the Department of the Theory of Gravity on January 26, 1973. (The seminar is lead by K. A. Piragas).